تشجيع االستثمار األجنبي فيالجزائر في ظل القانون 1 - بن شبحة مسعود - بوخروبةمحمد الصادق (المسيلة, 2023)
يعتبر االستثمار األجنبي عامال أساسيا وضروريا في تحقيق النمو االقتصادي والمساهمة بإصدار عدة قوانين لالستثمار آخرها القانون رقم في التنمية الوطنية، ألجل ذلك قامت الجزائر 18-22 الذي تضمن عدة ضمانات ومبادئ أساسية لالستثمار تم النص عليها في قوانين االستثمار السابقة، كما جاء بعدة ضمانات جديدة تدعم رغبة الدولة الجز ائرية في تشجيع االستثمار واستقطاب رؤوس األموال األجنبية. وقد عمد المشرع الجزائري إلى تحديث سياسة التحفيز الجبائي من خالل استحداث أنظمة تحفيزية جديدة، زيادة على ذلك، فقد تمت مراجعة المهام والصالحيات الممنوحة لألجهزة المكلفة باالستثمار، باإلضافة إلى استحداث هيئات وآليات جديدة تعمل على تسهيل العمليات االستثمارية، وذلك ألجل الرفع من جاذبية المناخ االستثماري في الجزائر وتشجيعا لالستثمار األجنبيForeign investment is considered as core essential factor for achieving economic growth and contributing to national development. Subsequently, Algeria has issued several investment laws including the latest of which is Law No. 18-22. It includes several guarantees and basic principles for investment that were stipulated in previous investment laws and, most importantly, it came with several new guarantees expressing the desire of the Algerian state to encourage investment and attract foreign capital. The legislator, as well, has updated the fiscal stimulus policy by introducing new incentive systems. In addition, the tasks and powers granted to the investment agencies have been reviewed. Furthermore, the law allowed the creation of new bodies and mechanisms to facilitate investment operations in order to boost attention around the investment climate in Algeria and encourage foreign investment.
Keywords: االستثمار، القانون 18-22، االست ثمار األجنبي، اللجنة، الوكالة، ضمانات االستثمار، األنظمة التحفيزية.